Institutional Quality and Sustainable Public-Private Investment in Zimbabwe’s Sanitation and Water Infrastructure - Mundonde, Justice; Takawira, Oliver (The Journal of Accounting and Management, 2025)
Abstract: Despite wide adoption in high income countries, Zimbabwe lags in implementing PPPs for WSS financing. Private players remain hesitant to take-up stake in WSS PPPs. Development Finance Institutions pointed out weak institutions to explain the trend. Limited scholarly work has been conducted on institutional quality and WSS PPPs in Zimbabwe. The current study covers this gap by analysing whether institutional variables impact WSS PPPs closure in Zimbabwe. Poisson regression analysis is applied on data collected between 1996 to 2021. Macro-economic, bank market and capital market variables supplemented the governance variables. The study concluded that WSS PPPs response to control of corruption. The relationship is inverse. Counter-intuitively government effectiveness, lawfulness and freedom of expression relates negatively to the number of PPPs that reached financial closure. Chinese soft diplomacy on Zimbabwe explains the finding. Government of Zimbabwe should strengthen its anti-corruption drive to enhance the attractiveness of WSS investments. Moreso, to attract institutionally elastic Western investors, the government of Zimbabwe must put in place strategies that enhance the country`s rule of law, voice and accountability and government effectiveness ranking. Other than institutional variables, evidence is provided that gross domestic product, the level of foreign direct investment, stock market capitalization, bank credit to deposit ratio and the level on non-performing loans influences water and sanitation PPP investments. Policy design should thus seek to stabilise Zimbabwe`s macroeconomic environment and foster bank and capital market development